Platinum(II) complexes based on derivatives of natural chlorins with pyridine-containing chelate groups as prototypes of drugs for combination therapy in oncology - N. S. Kirin; P. V. Ostroverkhov; M. N. Usachev; K. P. Birin; M. A. Grin (Тонкие химические технологии, 2024)
Objectives. To synthesize Pt-containing derivatives of natural chlorins as potential agents for the combination therapy in oncology. Platinum compounds are known to occupy an important place as chemotherapeutic agents in the treatment of oncological diseases. However, Pt(II) complexes are highly toxic to the body and are not selectively accumulated in tumor cells. If photodynamic and chemotherapy methods are combined in a single drug, the pigments are responsible for the selectivity of conjugate accumulation in the tumor, while a chemotherapeutic agent based on Pt(II) complexes is responsible for the cytotoxic effect on tumor cells. This will not affect healthy cells and thereby minimize the systemic toxicity of the drug to the body.Methods. Methods for the synthesis of pyridine-containing derivatives of natural chlorins and their metal complexes for use as potential binary agents in oncology were applied. As part of the study, the structures of the compounds obtained were confirmed by mass spectrometry, nuclear magnetic resonance spectroscopy, ultraviolet spectroscopy, and high-resolution chromatography-mass spectrometry. Preparative methods, including thin-layer and column chromatography, centrifugation and recrystallization, were used to isolate and purify the compounds obtained.Results. Platinum(II) complexes of pyridine-containing derivatives of natural chlorins were obtained for application in combination therapy in oncology. The schemes for synthesizing the target photosensitizers were optimized, in order to increase the yields and for subsequent transfer to industrial sites.Conclusions. It was found that pyridine-containing derivatives of natural chlorins could be obtained in high yields, that they possess chelating properties for platinum, and can be considered as binary agents in cancer therapy after successful preclinical trials.